The Significant Role of c-Abl Kinase in Barrier Altering Agonists-mediated Cytoskeletal Biomechanics - Wang, X. (Sci Rep, 2018)
Exploration of human pulmonary artery endothelial cell (EC) as a prototypical biomechanical system has important pathophysiologic relevance because this cell type plays a key role in the development of a wide variety of clinical conditions. The complex hierarchical organization ranging from the molecular scale up to the cellular level has an intimate and intricate relationship to the barrier function between lung tissue and blood. To understand the innate molecule-cell-tissue relationship across varied length-scales, the functional role of c-Abl kinase in the cytoskeletal nano-biomechanics of ECs in response to barrier-altering agonists was investigated using atomic force microscopy. Concurrently, the spatially specific arrangement of cytoskeleton structure and dynamic distribution of critical proteins were examined using scanning electron microscopy and immunofluorescence. Reduction in c-Abl expression by siRNA attenuates both thrombin- and sphingosine 1-phosphate (S1P)-mediated structural changes in ECs, specifically spatially-defined changes in elastic modulus and distribution of critical proteins. These results indicate that c-Abl kinase is an important determinant of cortical actin-based cytoskeletal rearrangement. Our findings directly bridge the gap between kinase activity, structural complexity, and functional connectivity across varied length-scales, and suggest that manipulation of c-Abl kinase activity may be a potential target for the treatment of pulmonary barrier disorders.